(untitled) (Ex Chordis, 2023)
This paper is a concise and updated version of my Bachelor’s Thesis, which explores Arvo Pärt’s primary violin compositions. After completing my Bachelor’s degree, my deep interest in the Estonian composer led me to attend the Arvo Pärt Days at the Arvo Pärt Centre in Laulasmaa, Estonia in 2022. Inspired by this immersive experience, I decided to revisit and expand upon my previous analysis of two specific violin pieces by Pärt: Tabula Rasa (1977) and Fratres (1980). I aim to increase the knowledge about Arvo Pärt without all the stereotypes linked to his music. Therefore, the study combines specificity and generality, offering insights that transcend the ordinary perceptions associated with Pärt’s music. Starting with an analysis of Pärt’s technique, I establish a foundation for understanding key concepts that will emerge in the subsequent analysis of Tabula Rasa and Fratres. As we explore these pieces, a thematic thread emerges, focusing on the violin’s role and its intricate interactions with different instruments. Arvo Pärt’s music is different from everything else: I hope to explain the deep reasons behind my passion for his work.